Investigating the link of ACAD10 deficiency to type 2 diabetes mellitus. Issue 1 (24th January 2017) - Bloom, Kaitlyn; Mohsen, Al‐Walid; Karunanidhi, Anuradha; El Demellawy, Dina; Reyes‐Múgica, Miguel; Wang, Yudong; Ghaloul‐Gonzalez, Lina; Otsubo, Chikara; Tobita, Kimi; Muzumdar, Radhika; Gong, Zhenwei; Tas, Emir; et al.
Abstract: The Native American Pima population has the highest incidence of insulin resistance (IR) and type 2 diabetes mellitus (T2DM) of any reported population, but the pathophysiologic mechanism is unknown. Genetic studies in Pima Indians have linked acyl‐CoA dehydrogenase 10 ( ACAD10 ) gene polymorphisms, among others, to this predisposition. The gene codes for a protein with a C‐terminus region that is structurally similar to members of a family of flavoenzymes—the acyl‐CoA dehydrogenases (ACADs)—that catalyze α, β‐dehydrogenation reactions, including the first step in mitochondrial FAO (FAO), and intermediary reactions in amino acids catabolism. Dysregulation of FAO and an increase in plasma acylcarnitines are recognized as important in the pathophysiology of IR and T2DM. To investigate the deficiency of ACAD10 as a monogenic risk factor for T2DM in human, an Acad ‐deficient mouse was generated and characterized. The deficient mice exhibit an abnormal glucose tolerance test and elevated insulin levels. Blood acylcarnitine analysis shows an increase in long‐chain species in the older mice. Nonspecific variable pattern of elevated short‐terminal branch‐chain acylcarnitines in a variety of tissues was also observed. Acad10 mice accumulate excess abdominal adipose tissue, develop an early inflammatory liver process, exhibit fasting rhabdomyolysis, and have abnormal skeletal muscle mitochondria. Our results identify Acad10 as a genetic determinant of T2DM in mice and provide a model to further investigate genetic determinants for insulin resistance in humans.